Riboswitch regulation of methionine metabolism and vitamin B12 uptake in mycobacteria – implications for drug susceptibility and pathogenesis - Kipkorir, Terry (Department of Pathology, 2020)
Alterations in the genetic capacity for cobamide biosynthesis have been identified as potentially critical in the evolution of Mycobacterium tuberculosis from a putative environmental ancestor. Moreover, recent studies have implicated cobamide biosynthesis pathway genes in the adaptation of the bacillus to intracellular pathogenesis. Although mycobacteria retain essential biochemical reactions that require cobamides, the specific role of these co-factors during tuberculosis (TB) disease remains unresolved. This thesis aimed to examine the production, uptake, and utilization of cobamides in mycobacteria using M. smegmatis as a model. To this end, the genetic capacity for de novo production and uptake of cobamide in host-associated and environmental mycobacteria was assessed, followed by direct validation in M. smegmatis. A combination of genetics, gene expression analysis, live-cell time-lapse microscopy and targeted metabolite and protein analysis via mass spectrometry (MS) was then employed to investigate cobamide riboswitch-dependent regulation of methionine biosynthesis in M. smegmatis. Results indicated that, in wild-type M. smegmatis, de novo cobamide biosynthesis ensured constitutive repression of metE, the gene encoding the mycobacterial cobalamin-independent methionine synthase. Owing to this repression, metH, a gene encoding the cobalamin-dependent methionine synthase, was found to be conditionally essential for bacillary replication in vitro. Drug susceptibility testing to investigate the link between cobamides and the intrinsic resistance to anti-folate antibiotics confirmed novel mycobacterial vulnerabilities in cobamide-related methionine metabolism, indicating that the outcomes of cobamidedependent regulation may have relevance to mycobacterial pathogenesis and drug discovery. In contrast to M. tuberculosis, which was previously shown to transport exogenous CNCbl readily, M. smegmatis poorly assimilated exogenous co-factor despite the presence of multiple putative cobamide transporters. However, uptake was enhanced in a mutant requiring CNCbl for growth. Elucidating the factors which regulate cobamide biosynthesis and co-factor utilization in M. smegmatis, an environmental mycobacterium, might provide a lens through which to consider the differential regulation and utilization of cobamides in M. tuberculosis, an obligate pathogen with a limited host range.